Recognition And Measurement Of Biological Assets Based On Psak 69 At Farm Layer Poultry Farm - Kevin Samuel Kodongan; Jullie Sondakh; Natalia Gerungai (PT. INOVASI TEKNOLOGI KOMPUTER, 2026)
This study aims to analyze the recognition and measurement of biological assets at the Kairos Farm Layer Poultry Farm in Noongan Village, West Langowan District, based on the provisions of PSAK 69, as well as its application in managerial decision-making. The research method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results indicate that the recognition of biological assets at Kairos Farm complies with PSAK 69 in terms of asset control and the generated economic benefits. However, in terms of measurement, the farm still utilizes the historical cost method due to the limitation of reliable market data to determine fair value. Despite the constraints in this fair value measurement, information regarding the acquisition cost and the value of biological assets proves to be a crucial basis for management in cost planning, expenditure control, and business performance evaluation. A more comprehensive implementation of PSAK 69 in the future is expected to improve the accuracy of financial statements and the effectiveness of decision-making